Sorry angel [videorecording (DVD)] - Honoré, Christophe, 1970-; Honoré, Christophe, 1970-; Lacoste, Vincent; Deladonchamps, Pierre; Podalydès, Denis, 1963- (Strand Releasing Home Video, 2019)
A middle-aged author, on the verge of suicide, meets and falls in love with a young man.